Exploring Antimicrobial Resistance in Bacteria from Fecal Samples of Insectivorous Bats: A Preliminary Study - Santina Di Bella; Delia Gambino; Maria Foti; Bianca Maria Orlandella; Vittorio Fisichella; Francesca Gucciardi; Francesco Mira; Rosario Grasso; Maria Teresa Spena; Giuseppa Purpari; Annalisa Guercio (Veterinary Sciences)
Bats (order Chiroptera) are increasingly recognized as important reservoirs and potential vectors of pathogenic and antimicrobial-resistant bacteria (ARB), with potential implications for human, animal, and environmental health. This study aimed to assess the presence and antimicrobial resistance profiles of bacterial isolates from bat populations in Sicily, an area for which data are currently limited. A total of 132 samples (120 rectal swabs and 12 guano samples) were collected at four sites in the provinces of Catania, Siracusa, and Ragusa. Bacteriological analysis yielded 213 isolates, including 161 Gram-negative and 52 Gram-positive strains, representing 55 different species. Among Gram-negative isolates, Escherichia coli, Citrobacter freundii, and Morganella morganii were most frequently detected, while Bacillus licheniformis and Staphylococcus xylosus were predominant among Gram-positive bacteria. Antimicrobial susceptibility testing revealed high resistance rates to colistin, amoxicillin, and ampicillin in Gram-negative strains, and to oxacillin, ceftazidime, and lincomycin in Gram-positive strains. Notably, 84.5% of isolates exhibited multidrug resistance. These findings highlight the potential role of bats as reservoirs of ARB and underline the importance of ongoing monitoring within a One Health framework to mitigate risks to public and animal health.